Pengembangan Bahan Ajar berbasis Modul PAI Perspektif Imam Al-Ghozali pada Siswa Inklusi - Awaliya Nurul Iksan; Machnunah Ani Zulfah (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2022)
This study discusses the development of teaching materials based on the Islamic education module from Imam Al-Ghozali's Perspective for Class VIII Inclusion Students at SMP Sunan Ampel Jombang. Ampel Jombang, 2) The effectiveness of PAI teaching materials for Class VIII Inclusion Students at Sunan Ampel Junior High School. In line with the growing demands of the ABK group in voicing their rights, the concept of inclusive education emerged. On this occasion the researchers developed teaching materials in the form of PAI Modules to be developed. This study uses the Dick & Carey model of R&D development research. Sources of data used are primary and secondary data, where primary data are PAI subject teachers and inclusive students, while secondary data are documentation, textbooks, school archives. The results validation of material experts 86 persen, media expert validation 91 persen, questionnaires for inclusion students 95 persen, then the results of post-test and pre-test trials with a calculation system. the N-Gain formula obtained a score of 0.8 higher post-test scores than the pre-test scores. So the textbooks that have been made are very suitable for use by inclusive students.